Kombinasi Semi Fowler dan Pursed Lip Breathing terhadap Stabilisasi Respirasi pada Pasien Gagal Jantung: Studi Kasus - Fika Dwilianti Sakri; Dwiyanti Purbasari (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
The prevalence of heart disease in Indonesia is 1.5% and in West Java 1.6%, with acute decompensated heart failure (ADHF) being one of the cardiovascular conditions that frequently requires hospitalization. ADHF is a condition characterized by a sudden or gradual worsening of heart failure symptoms that can cause shortness of breath. Objective: To determine the effect of a combination of the semi-Fowler position and pursed-lip breathing on respiratory stabilization in patients with ADHF. Research method: Qualitative research using a case study design. The sample consisted of 2 individuals with a medical diagnosis of ADHF and a nursing diagnosis of ineffective breathing pattern. The research procedure involved assessment through history-taking, inspection, palpation, percussion, and auscultation; implementation of the semi-Fowler position and pursed-lip breathing; and evaluation of respiratory stabilization. The study was conducted over three days, from February 23 to 25, 2026, in the ICCU ward at Gunung Jati Regional General Hospital. Research findings: The nursing diagnosis based on the SDKI for both respondents was ineffective breathing pattern; data from both respondents indicated complaints of shortness of breath, increased respiratory rate, use of accessory breathing muscles, and decreased oxygen saturation. After implementing the semi-Fowler position and pursed-lip breathing, respiratory stabilization occurred, with shortness of breath improving, respiratory rate improving, use of accessory breathing muscles decreasing, and oxygen saturation improving. Conclusion and Recommendations: The combination of the semi-Fowler position and pursed-lip breathing can help stabilize respiration in patients with shortness of breath. It is hoped that the combination of the semi-Fowler position and pursed-lip breathing can be implemented as a safe and simple nonpharmacological nursing intervention to help stabilize respiration in patients with respiratory disorders, particularly heart failure.